Choreographing a Massacre: Memory and performance of the Accomarca Massacre in the Ayacuchan Carnival in Lima, Peru - Aroni, Renzo (2015)
On August 14, 1985, during the long internal armed conflict between the Maoist guerrilla group Sendero Luminoso and the Peruvian state, an army patrol entered the Andean town Accomarca, located in the Ayacucho region, and killed 69 indigenous people, including children and elderly, alleged supporters of the insurgent group. The majority of survivors and relatives of victims were displaced to Lima and integrated into the victims’ organization and the Asociación Hijos del Distrito de Accomarca - AHIDA. Since 2011, on the occasion of the extradition from the United States of Lieutenant Telmo Hurtado, main person responsible of the massacre, the AHIDA has recreated the painful experience of the massacre through an annual Ayacuchan Carnival performance incor- porating choreography and testimonial songs to demand justice for the victims of the massacre. In addition, this carnivalesque performance involves children and young people who did not lived the massacre, but imagine, interpret and create their own memory by communicating with the survivors and participating in the cultural production of the event. In this article, I expose how survivors and relatives of victims remember the massacre and transmit their memories to their children through a carnivalesque performance. I describe the production of an intergenerational memory through the intergenerational transmission, which is constructed in the domestic space (family), the communal/institutional space (AHIDA), and the public space (Carnival). Surely, the occasion of the Carnival is a powerful spacefor the production of other forms of memory, and for the demand for justice through participatory choreographic and musical performance.